Congruency and phenotypic plasticity of immune and nervous systems in children with autism spectrum disorders compared to schizophrenia spectrum disorders”, Medical Immunology (Russia) - A. L. Burmistrova; Yuliya Yu. Filippova (Медицинская иммунология, 2020)
According to new views on communication ways and  principles in the main  regulatory systems of the  body, i.e.,  immune and  neuroendocrine, there  is a risk for disintegration of pathways  and  structures in these  systems which  may underlie disorders  such as autism-spectrum disorders  (ASD)  and schizophreniaspectrum disorders (SSD). Both disorders are classified as neurodevelopmental disorders, with unclear etiology and partially  overlapping pathophysiological developmental mechanisms. Diagnosis of ASD and SSD is based on patterns of clinical  symptoms/syndromes that  demonstrate high heterogeneity and  similarity.  Therefore, it is very important to find the  ways of discerning children with ASD from  those  with SSD.  Our  aim was to identify peripheral activity indexes for immune and neuroendocrine systems, and their integration for usage as information hubs of congruency and phenotypic plasticity of these systems in children with ASD, as compared to SSD  patients. The  levels of 14 indexes  of the immune and  neuroendocrine systems in blood  plasma  were determined in 82 children with ASD, 9 children with SSD and 45 children with typical neurodevelopment (TD). To assess peripheral activity of the immune and neuroendocrine systems and their relationships, we applied  a multivariate exploratory analysis using a method of nonlinear principal components. The following results were obtained: (1) absence  of differences in proinflammatory cytokines between  ASD and TD children; (2) patients with SSD  have significantly  higher  values of IL-6  and IFNγ, and lower values of IL-1β, TNFα and IL-10  in blood plasma compared to children with ASD and TRD; (3) the level of neurohormones in children with ASD is in accordance with physiological reference values. The children with SSD have lower levels of epynephrine and dopamine compared to ASD and TD,  respectively; (4) integration degree of regulatory systems assessed by principal component analysis has shown  the following:  (4.1)  TD  children have strong  correlations within each of the systems and between  them, thus showing their communicative abilities and plasticity, characteristic of normal values; (4.2) In SSD  children, minimal numbers of strong  relations were demonstrated within  the cytokine system;  (4.3)  The children with ASD exhibited  two clusters:  one of them  had a complete similarity with TDC, in terms of tension and assortment of immune and neuroendocrine indices; the other one presented low coupling between  the parameters of regulatory systems, similar to the children with SSD; (4.4) Analysis of peripheral indices of cytokine and neuroendocrine systems for clusters 1 and 2 in children with ASD compared to children with SSD and TD demonstrated that,  in children with ASD of cluster  1, the indices  did not differ from TDC, except  of epinephrine, ACTH, kynurenine, and tryptophan. In the children with ASD of cluster 2, the values of the indices are equal to children with SSD,  except of dopamine and tryptophan. Thus,  we have shown phenomenon of transdiagnostic clustering, i.e., allocation of two clusters among  ASD children. One of them is similar to levels of indices and connections between the immune and neuroendocrine systems with TD, and another cluster is similar to SSD children. Therefore, they could be potentially useful as diagnostic criteria when discriminating the two disorders.